ANALISIS NILAI TAMBAH, HARGA POKOK PRODUKSI, DAN KEUNTUNGAN AGROINDUSTRI SAMBAL TEMPOYAK (STUDI KASUS PADA AGROINDUSTRI MAUGI DI KOTA JAMBI) - Simanjuntak, Sara Gracia; Lestari, Dyah Aring Hepiana; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This research intended to analyze the added value, the cost of goods sold, and the profit of Sambal Tempoyak Agroindustry. The method used was case study at Maugi Agroindustry in Alam Barajo District, Jambi City. Maugi Agroindustry is an agroindustry that actively produces sambal tempoyak, therefore the location of the research was chosen purposefully. Owners and employees of Maugi Agroindustry participated in this study as respondents. Data collection for this study was carried out from December 2022 to January 2023, and the data gathered was analyzed by employing descriptive qualitative and quantitative methods. The data required for this research were primary data from observations and questionnaires as well as secondary data from related literatures. In analyzing data, Hayami added value method and full costing method were utilised. Based on the research results, it is known that the Maugi Agroindustry producing sambal tempoyak in bottles of 200 grams, 150 grams, and 40 grams. It generates profits because the added value is greater than zero, so it is feasible to develop. The selling price of each package based on the Maugi Agroindustry policy is above the production cost which is calculated using the full costing method. The highest profit is for the 200 grams glass bottle sambal tempoyak and the lowest profit is for the 40 grams bottle sambal tempoyak. Keywords: added value, cost, profit, sambal tempoyak